A Polarization Dependent Electromagnetic Band Gap based Circularly Polarized Low Profile Dipole Antenna for WLAN Application: Circularly Polarized Low Profile Dipole Antenna for WLAN Application - Khan, Asaf; Bashir, Shahid; Khan, M. Salman; Ullah, Khadim (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This paper presents circularly polarized dipole antenna operating at 5.8 GHz for WLAN applications. Normally dipole antenna radiates linearly polarized waves. Radiation of circularly polarized (CP) wave has been achieved through integration of a novel PDEBG with the antenna. PDEBG are artificial structures that show diversity in reflection phase depending on the polarization state of incident plane wave. This polarization dependent reflection phase feature of PDEBG is realized by modifying its rectangular unit geometry. It has been observed that proposed dipole antenna has an axial ratio less than 3 dB in frequency range from 5.58 GHz to 5.93 GHz (AR BW= 5.98%). The proposed PDEBG structure has 6.02% wider frequency bandwidth for linear to circular polarization and an overall size reduction of 15% as compared to previously proposed PDEBG structures. The proposed PDEBG can be used for reconfigurable polarization surfaces.